Coccidiosis amongst calves. 1. A relation between oocysts per gram faeces and faecal consistency - Bhattacharya, D; Sikdar, A; Roy, P K; Ghosh, A; Mishra, R K (The Indian Journal of Animal Sciences, 2012)
Clinical cases of eimenosis exhibiting diarrhoeic syndrome were diagnosed in calves. In general, animals shedding over 2000 oocytes were showing only the symptoms of diarrhoea. Reexamination of faecal samples has been recommended after 9 days from the onset of diarrhoea in unusual cases. Age-wise variation of the oocyst count from 10 diarrhoeic cases revealed presence of 3 species, viz. Eimeria bovis (23.95 %), E. zuernii (46.12 %) and E. subspherica (29.93%).